Perspectives on International Urological Volunteerism: A Survey of IVUmed Resident Scholar Alumni. Issue 2 (March 2017) - Murthy, Prithvi; Malik, Rena D.; McCammon, Kurt A.; Schneck, Francis X.; deVries, Catherine; Chrouser, Kristin; Eggener, Scott E.
ABSTRACT : Introduction: : The primary intentions of international surgical programs are to directly benefit those receiving medical care, educate local physicians and staff, and improve care delivery models. IVUmed, a nonprofit organization dedicated to providing urological care to resource poor areas of the world, provides scholarship opportunities for urology trainees. We assessed the motivations and barriers of IVUmed traveling resident scholars regarding continuing international surgical work after completion of the program. Methods: : An Internet based survey was sent to all previous IVUmed resident scholars assessing potential factors associated with repeat international service. Logistic regression was used to examine the association between survey responses and the likelihood of repeating an international service trip after completion of training. Results: : Of 196 IVUmed resident scholar participants 100 (51%) responded to the survey. Of the 69 attending surgeons 17 (25%) had repeated an international service trip. Altruism (100%), personal fulfillment (99%) and practicing in a resource limited setting (94%) were the most frequently cited motivating factors for repeat participation, while lack of time (96%) was the most commonly reported barrier. Respondents in private practice were less likely to participate in a subsequent trip compared to those in an academic setting (OR 0.16, CI 0.03–0.80, p = 0.03). No other factors were associated with the likelihood of repeating an international service trip. Conclusions: : Among urologists who participated in a funded international scholarship program during residency repeat participation during the subsequent 7 years was modest. Private practitioners were less likely to repeat international service compared to academic urologists.